Buckling of elastic circular plates with an elastically restrained edges against rotation and internal elastic ring support - Bhaskara Rao, L.; Kameswara Rao, C. (Прикладная механика, 2015)
The buckling of elastic circular plates with an internal elastic ring support and elastically restrained edges against rotation and simply supported is concerned. The classical plate theory is used to derive the governing differential equation. This work presents the existence of buckling mode switching with respect to the radius of internal elastic ring support. The plate may buckle in an axisymmetric mode in general, but when the radius of the ring support becomes small, the plate may buckle in an asymmetric mode. The cross-over ring support radius varies from 0.09891 to 0.1545 times the plate radius, depending on the rotational stiffness of the elastic restraint at the edges and elastic restraint of the ring. The optimum radius of the internal elastic ring support for maximum buckling load is also determined. Extensive data is tabulated so that pertinent conclusions can be arrived at on the influence of rotational restraint, translational restraint of internal elastic ring support, Poisson’s ratio, and other boundary conditions on the buckling of uniform isotropic circular plates. The numerical results obtained are in good agreement with the previously published data. Розглянуто випучування пружної круглої пластинки з внутрішнім кріпленням у вигляді пружного кільця і зовнішньою границею, яка обмежує пружне обертання і є вільно опертою. Виведено диференціальні рівняння, що описують задачу, для чого використано класичну теорію пластинок. Запропоновано доведення існування перемикання на моду випучування в залежності від радіуса внутрішнього кільця. Пластинка може випучуватися, взагалі кажучи, за осесиметричною модою, але для малого радіуса кільця пластинка може випучуватися за неосесиметричною модою. Перехідне значення відношення радіуса кільця до радіуса пластинки змінюється від 0,9891 до 0,1545 в залежності від жорсткості кільця і обмеження на обертання на зовнішній границі пластинки. Також визначено максимальний радіус кільця, пов'язаний з максимальним значенням навантаження. Числові дані згруповані таким чином, що вони дозволяють зробити висновки щодо впливу обмеження на обертання, обмеження на поступальний рух кільця, коефіцієнта Пуассона та інших граничних умов на випучування однорідної круглої пластинки. Отримані числові результати добре узгоджуються з даними, опублікованими раніше.